Anti-corrosion and anti-stick coating and its application
By applying neutral or weakly alkaline anti-corrosion and anti-adhesive coatings on the surface of the ceramic roller, the corrosion and adhesion problems caused by the liquefaction of the iron oxide sheet and FeAlSi ternary alloy phase during the high-temperature thermoforming steel formation process are solved. , extends the service life of ceramic rollers and improves its corrosion resistance.
Patent Information
- Application Number
- CN202310804794.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-03
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-07-03
AI Technical Summary
During the hot pressing process of high-temperature hot-forming steel, existing ceramic rollers have corrosion and adhesion problems due to the formation of iron oxide sheet and the liquefaction of FeAlSi ternary alloy phase, resulting in short service life and uneven operation of ceramic rollers, which affects the automotive frame. Dimensional accuracy and appearance quality of components.
Neutral or weakly alkaline anti-corrosion and anti-stick coatings, the coating includes base material and fabric, which is applied to the surface of the ceramic roller by spraying or brushing. The composition of the base material and fabric ensures that the coating is not easy to be with the ternary alloy. Phase reaction extends the service life of the ceramic roller.
The service life of ceramic rollers is extended to about 5 months, which improves the corrosion resistance and surface smoothness of ceramic rollers, reduces the adhesion and corrosion of the liquefied alloy phase, and ensures the dimensional accuracy and appearance quality of the automotive frame components.
Smart Images

Figure FT_1 
Figure FT_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rollers for roller-bottom kilns, and in particular relates to an anti-corrosion and anti-sticking coating and an application thereof.
[0002] The present invention belongs to the 3.1 new functional materials industry key direction 3.1.5 surface functional materials and high temperature ceramic coating materials in the 3 new materials industry of the catalog of strategic emerging industries. Background Art
[0003] Hot-formed steel has irreplaceable advantages in solving the problem of lightweighting automobiles and stamping high-strength steel. However, in the hot stamping process, since the material needs to be heated to a temperature of 950°C or above, this will cause oxidation on the surface of the material and a large amount of iron oxide scale will appear. In order to avoid oxidation, the product is produced by adding an aluminum-silicon coating. The automotive frame components in the automotive industry (such as A-pillars, B-pillars, frames, doors, etc.) are formed by hot pressing at 900-950°C in a roller-bottom kiln using aluminum-silicon coated hot-formed steel plates. After forming, they must undergo annealing treatment in a roller-bottom kiln at the same temperature. When the temperature exceeds 900°C, metal rollers cannot be used in the roller-bottom kiln, and only oxidation-resistant alumina ceramic rollers can be used. During the heating process, the Fe element in the aluminum-silicon coating matrix diffuses to the coating surface to form a FeAlSi ternary alloy phase, and the coating liquefies and has a certain fluidity. This liquefied ternary alloy has a strong corrosive effect on the ceramic roller of the roller hearth kiln, reducing the service life of the ceramic roller. At the same time, the liquefied alloy phase in blocks adhering to the ceramic roller will also cause the running surface of the ceramic roller to be uneven, causing the automobile frame components to move forward in a bumpy manner, resulting in dimensional deviation problems, and may also cause scratches on the metal surface and other appearance problems, causing trouble for subsequent production.
[0004] At present, the main ceramic rollers used in roller furnaces in the domestic metal heat treatment industry are the first type. They are ordinary domestic ceramic rollers without anti-corrosion coatings and are low in price. They are mostly oxidation products of the AlSi mineral group and belong to the corundum-mullite composite phase structure. For example, the Chinese patent application number 202110879468.2 discloses an ultra-high temperature ceramic roller for a roller kiln. Although its aluminum content is as high as 90%, due to the use of 10-14% silicon micropowder in its raw materials, mullite phase is bound to be generated during the firing process. Among them, the mullite (3Al2O3·2SiO2) phase is easily corroded by alkali metal substances and decomposed into corundum phase and impurity phase, which fundamentally destroys the structure of conventional rollers, thereby causing the rollers to break. Depending on the quality of the rollers and the use environment, without coating protection, the surface adhesion of the FeAlSi ternary alloy phase is serious, see Figure 1 , it will break in 1-2 days at the fastest and 10 days at the slowest.
[0005] The second type is a ceramic roller with a conventional coating. The current conventional coatings either fail to meet the use requirements of 500-1000°C, and some that can meet the temperature requirements are generally single-layer acidic oxide coatings. Although they can play a certain role in protecting ceramic rollers, the FeAlSi ternary alloy mixture is an alkaline substance and is very easy to react with the acidic coating to produce an acid-base neutralization reaction; and the surface smoothness of the above coating is not enough, with a surface roughness of approximately Rz=50. The low surface smoothness causes the FeAlSi ternary alloy mixture to easily adhere to the coating surface, corroding and destroying the coating. Therefore, the conventional ceramic roller with this coating has a lifespan of about 1-2 months depending on the quality and use environment.
[0006] The third type is imported ceramic rollers with anti-corrosion and anti-adhesion coatings, which can generally be used for 4-6 months, but the price is extremely high, 8-10 times that of domestic ceramic rollers. Summary of the invention
[0007] In view of the above problems existing in the prior art, the present invention provides an anti-corrosion and anti-stick coating and its application. The coating is neutral or weakly alkaline. After being applied on the surface of the ceramic roller to form a coating, it is not easy to react with the ternary alloy phase, so that the coating and the alloy phase will not stick together due to chemical reaction, thereby protecting the ceramic roller body and extending the service life of the ceramic roller.
[0008] The object of the present invention is achieved in the following manner:
[0009] A corrosion-resistant and anti-stick coating comprises a base material and a surface material, wherein the base material comprises 40-50 parts of alkaline silica sol, 28-35 parts of neutral or alkaline α-alumina powder, 15-25 parts of titanium dioxide, 1-3 parts of china clay, 0.3-0.5 parts of sodium carboxymethyl cellulose, and 1-3 parts of polyethylene glycol; the surface material comprises 50-70 parts of alkaline silica sol, 6-15 parts of neutral or alkaline α-alumina powder, 10-20 parts of hexagonal boron nitride, 6-15 parts of titanium dioxide, 0.6-0.8 parts of sodium carboxymethyl cellulose, and 1-3 parts of polyethylene glycol.
[0010] The alkaline silica sol has a pH value of 8-10, an average particle size of 10-20 nm, and a SiO2 content of 25-40%.
[0011] The pH value of the neutral or alkaline α-alumina powder is ≥7.5, the Al2O3 content is ≥99.5%, the average particle size is ≤2.5 μm, and the conversion rate is ≥95%.
[0012] The titanium dioxide has a TiO2 content of ≥98%, a pH value of ≥7, and an overall fineness of ≤45 μm.
[0013] The purity of the hexagonal boron nitride is ≥99.4%. The hexagonal boron nitride is composed of two types: HC type with an average particle size of 9 μm and HS type with an average particle size of 35 μm. The two types of hexagonal boron nitride are mixed in a ratio of 1:1, 1:2, and 1:3.
[0014] The anti-corrosion and anti-stick coating is coated on the surface of a ceramic or metal substrate, the ceramic is corundum ceramic or AlSi ceramic, and the metal is aluminum, aluminum alloy, stainless steel, or heat-resistant steel.
[0015] The substrate is in the shape of a tube, a rod or a plate.
[0016] A corundum ceramic roller, the surface of which is coated with the above-mentioned anti-corrosion and anti-sticking coating.
[0017] The raw materials in the base material and the surface of the anti-corrosion and anti-stick coating are mixed evenly according to the proportion, and the slurry concentration of the base material and the surface is adjusted with an appropriate amount of deionized water. The slurry pH value of the base material and the surface is ≥7.5. The base material and the surface are coated on the surface of the ceramic roller by spraying, brushing or pouring. The base material is coated first, and the surface is coated after the base material is half dry. The base material and the surface are naturally dried after coating.
[0018] The viscosity of the base material and the surface material slurry is adjusted to 2-7Pa.s.
[0019] The thickness of the base coating is 0.1-0.25μm, and the thickness of the surface coating is 0.3-0.45μm.
[0020] The ceramic roller body contains the following main raw materials by weight: 70-90 parts of alpha alumina powder, 1-3 parts of activated alumina powder, 10-30 parts of plate-like corundum, 0.5-1.5 parts of stabilized yttrium oxide; auxiliary materials: 0.2-1 parts of hydroxypropyl methylcellulose, 0.5-2.5 parts of sodium carboxymethyl cellulose, 3-5 parts of edible oil, and 12-13 parts of water.
[0021] The method for preparing the corundum ceramic roller comprises the following steps:
[0022] (1) Mix α-alumina powder, activated alumina powder, plate-shaped corundum and stabilized yttrium oxide in proportion and put them into a mixer to mix evenly;
[0023] (2) During the mixing process, hydroxypropyl methylcellulose and sodium carboxymethyl cellulose dissolved in water are evenly sprayed into the mixer several times;
[0024] (3) The mixed raw materials are put into the vacuum clay machine for vacuum exhaust and uniform mixing. During this process, edible oil as extrusion lubricant is evenly added, and then extruded into shape in the vacuum extruder with an extrusion pressure of 20-25 bar;
[0025] (4) After drying, it is fired upright in a kiln at a temperature of 1650-1700℃.
[0026] Step (4) drying refers to natural drying at room temperature for 3 days, then slowly raising the drying room temperature to 45-50°C and drying for 2 days.
[0027] Step (4) bottom-standing firing means laying 2-3 cm thick fused corundum sand on the bottom of the kiln car table. The blank is placed on the corundum sand for easy leveling and vertical to the kiln car table. Recrystallized silicon carbide brackets are used every 50-100 cm along the length of the blank to fix the blank at multiple points on the side of the blank so that it does not move and does not deviate from the position vertical to the kiln car table.
[0028] Compared with the prior art, the raw materials used for the base material and the surface material of the anti-corrosion and anti-stick coating disclosed in the present invention are neutral or weakly alkaline, and the coating as a whole is also neutral or weakly alkaline, which is not easy to react with the ternary alloy phase, so that the coating and the alloy phase will not chemically react and stick together. The surface roughness of the ceramic stick coated with the anti-corrosion and anti-stick coating is Rz≤6.3, which is nearly 10 times different from the surface roughness of the ceramic stick coated with the conventional coating Rz=50. Since the surface of the anti-corrosion and anti-stick coating is smooth, the liquefied ternary alloy phase will slide directly after dripping on the coating, and will not stay on the surface of the coating, or the stay time is very short. Since the contact time between the liquefied ternary alloy phase and the coating is very short, it is not easy to react with the coating, and it is not easy to corrode the coating, thereby extending the service life of the ceramic roller. The anti-corrosion and anti-stick coating disclosed in the present invention is a water-based coating, non-toxic and easy to clean; high temperature resistance, good lubricity and inertness are maintained at high temperatures, the maximum use temperature in an oxidizing atmosphere is 1000°C, and the maximum use temperature in an inert or reducing atmosphere is 2200°C. The anti-corrosion and anti-stick coating disclosed in the present invention comprises two layers, namely a base material layer and a surface material layer. The two layers of coating cooperate to extend the service life of the ceramic roller in the roller furnace to about 5 months. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic diagram of the surface of an uncoated ceramic roller after bonding the ternary alloy phase.
[0030] Figure 2 Schematic diagram of a coated ceramic roller surface without a ternary alloy phase bonded thereto. DETAILED DESCRIPTION
[0031] An anti-corrosion and anti-stick coating comprises a base material and a surface material, wherein the base material comprises 40-50 parts of alkaline silica sol, 28-35 parts of neutral or alkaline α-alumina powder, 15-25 parts of titanium dioxide, 1-3 parts of china clay, 0.3-0.5 parts of sodium carboxymethyl cellulose, 1-3 parts of polyethylene glycol, and some deionized water; the surface material comprises 50-70 parts of alkaline silica sol, 6-15 parts of neutral or alkaline α-alumina powder, 10-20 parts of hexagonal boron nitride, 6-15 parts of titanium dioxide, 0.6-0.8 parts of sodium carboxymethyl cellulose, 1-3 parts of polyethylene glycol, and some deionized water, wherein the deionized water is used as a solvent to adjust the slurry concentration of the base material or the surface material. The silica sol is preferably alkaline silica sol with a pH of 8-10, an average particle size of 10-20nm, and a SiO2 content of 25-40%; the α-alumina powder is preferably neutral or alkaline α-alumina powder with a pH of ≥7.5, an Al2O3 content of ≥99.5%, an average particle size of ≤2.5μm, and a conversion rate of ≥95%; the titanium dioxide is preferably titanium dioxide with a TiO2 content of ≥98%, a pH of ≥7, and an overall fineness of ≤45μm; the purity of hexagonal boron nitride is ≥99.4%, and the HC type with an average particle size of 9μm and the HS type with an average particle size of 35μm are preferred. The two types of hexagonal boron nitride are used in a ratio of 1:1, 1:2, or 1:3.
[0032] Hexagonal boron nitride uses two different particle sizes, HC and HS, because the two different particle sizes are evenly and reasonably graded, the coating surface packing density is good, more airtight, so that the coating has a low porosity, is more resistant to metal friction during use, and has a long service life.
[0033] Application of anti-corrosion and anti-stick coating, the anti-corrosion and anti-stick coating is applied on the surface of ceramic or metal substrate, the ceramic is corundum ceramic or AlSi ceramic, the metal is aluminum, aluminum alloy, stainless steel, heat-resistant steel. The substrate is in the shape of pipe, rod, plate.
[0034] A corundum ceramic roller, the surface of which is coated with the above-mentioned anti-corrosion and anti-sticking coating.
[0035] The coating method of the anti-corrosion and anti-stick coating on the surface of the corundum ceramic roller comprises the following steps: mixing the raw materials in the base material and the surface material respectively in proportion, adjusting the slurry concentration of the base material and the surface material respectively with deionized water, and adjusting the viscosity to between 2-7 Pa.s according to the coating working surface conditions, firstly trial coating a small area, and then spraying, brushing or pouring the coating on the surface of the ceramic roller body when a large amount of coating is carried out, first coating the base material, and then coating the surface material after the base material is semi-dry. Before trial coating, it is best to use a pH value reagent or test paper to detect the base and surface slurries to ensure that the pH value is above 7.5. According to different climate conditions in different places, it generally takes 15-25 minutes in summer for the base material to reach semi-dryness, and 30-50 minutes in winter. When the base material does not reach semi-dryness, the surface material coating cannot be applied. The base material coating thickness is 0.1-0.25 μm, and the surface material coating thickness is 0.3-0.45 μm. After coating, the base material and fabric can only be dried naturally. Do not add air or heat to dry or expose to the sun to prevent the coating from cracking.
[0036] The viscosity of the base material and the surface material slurry is adjusted to 2-7Pa.s.
[0037] The thickness of the base coating is 0.1-0.25μm, and the thickness of the surface coating is 0.3-0.45μm.
[0038] A corundum ceramic roller, the ceramic roller body contains the following main raw materials in parts by weight: 70-90 parts of alpha alumina powder, 1-3 parts of active alumina powder, 10-30 parts of plate-shaped corundum, and 0.5-1.5 parts of stabilized yttrium oxide; the percentage of each auxiliary material to the total weight of the main raw material is: 0.2-1 parts of hydroxypropyl methylcellulose, 0.5-2.5 parts of sodium carboxymethyl cellulose, 3-5 parts of edible oil, and 12-13 parts of water.
[0039] The Al2O3 content of α-alumina micropowder is ≥99.5%, the Na2O content is ≤0.06%, the particle size is preferably <2μm and <5μm, and the conversion rate is 95%; the particle size of activated alumina powder is <1μm, and the conversion rate is 90-93%. Stabilized yttrium oxide is a rare earth element compound, yttrium oxide with a cubic structure.
[0040] The preparation method of a corundum ceramic roller comprises the following steps: (1) α-alumina micropowder, plate-shaped corundum, activated alumina powder and yttrium oxide are prepared in the above proportions and put into a mixer for uniform mixing; (2) during the mixing process, hydroxypropyl methylcellulose and sodium carboxymethyl cellulose dissolved in water are evenly sprayed into the mixer in multiple times; (3) the mixed raw materials are put into a vacuum clay kneading machine for vacuum exhaust and uniform mixing, and edible oil as an extrusion lubricant is evenly added during this process, and then extrusion molding is carried out in a vacuum extruder at an extrusion pressure of 20-25 bar; (4) natural drying is carried out at room temperature for 3 days, and then the temperature of the drying room is slowly increased to 45-50°C and dried for 2 days. After drying, the blank is fired upright in the kiln. A 2-3 cm thick layer of fused corundum sand is laid on the bottom of the kiln table. The blank stands on the corundum sand for easy leveling and vertical positioning. In the length direction of the product, recrystallized silicon carbide brackets are used every 50 cm to 100 cm to fix the product at multiple points on the side of the product so that it does not move and does not deviate from the position vertical to the kiln table. The firing temperature is 1600-1700℃.
[0041] After the base material and the surface are dried, the surface of the anti-corrosion and anti-stick coating is smooth. Figure 2 The surface roughness of the corundum ceramic roller coated with the anti-corrosion and anti-stick coating is Rz≤6.3 as measured by a roughness detector with an accuracy of 0.01. Compared with the roughness of the conventional ceramic roller without coating and the roughness of the ceramic roller with conventional coating, the roughness of the conventional ceramic roller without coating is Rz≥200, and the roughness of the ceramic roller with conventional coating is about Rz=50. The roughness of the corundum ceramic roller with the anti-corrosion and anti-stick coating disclosed in the present invention is much lower than the roughness of the conventional ceramic roller without coating and the roughness of the ceramic roller with conventional coating.
[0042] Example 1
[0043] Anti-corrosion and anti-stick coating
[0044] An anti-corrosion and anti-stick coating, wherein the base material comprises 45 kg of silica sol, 35 kg of alumina powder, 15 kg of titanium dioxide, 2 kg of porcelain clay, 0.4 kg of sodium carboxymethyl cellulose, and 2 kg of polyethylene glycol; the surface material comprises 60 kg of silica sol, 10.5 kg of neutral or alkaline α-alumina powder, 10.5 kg of titanium dioxide, and 18 kg of hexagonal boron nitride, wherein the ratio of HC type to HS type is 1:1, 0.7 kg of sodium carboxymethyl cellulose, and 2 kg of polyethylene glycol.
[0045] Preparation of corundum ceramic roller:
[0046] The main ingredients are 80 kg of α-alumina micropowder, 20 kg of plate-shaped corundum, 2 kg of activated alumina powder, and 1 kg of stabilized yttrium oxide; auxiliary materials: 0.6 kg of hydroxypropyl methylcellulose, 1.5 kg of sodium carboxymethyl cellulose, 4 kg of edible oil, and 13 kg of water.
[0047] (1) Alpha alumina powder, plate-shaped corundum, activated alumina powder and stabilized yttrium oxide are prepared in the above proportions and put into a mixer for uniform mixing; (2) During the mixing process, hydroxypropyl methylcellulose and sodium carboxymethyl cellulose dissolved in water are sprayed evenly into the mixer several times; (3) The mixed raw materials are put into a vacuum clay kneading machine for vacuum exhaust and uniform mixing. During this process, edible oil as an extrusion lubricant is evenly added, and then extruded into a vacuum extruder at an extrusion pressure of 25 bar; (4) Dry naturally for 3 days at room temperature, then slowly increase the temperature of the drying room to 50°C and dry for 2 days. After drying, the blank is fired upright in the kiln, and 2-3 cm thick fused corundum sand is laid on the bottom of the kiln car table. The blank is easy to level and vertical to the kiln car table when it stands on the corundum sand. In the length direction of the blank, a recrystallized silicon carbide bracket is used every 80 cm to fix the blank from multiple points on the side of the blank so that it does not move and does not deviate from the position vertical to the kiln car table. The firing temperature is 1680±5°C. After testing, the flexural strength of the corundum ceramic roller produced by the above process reaches ≥220MPa, and the tensile strength reaches ≥300MPa; the water absorption rate is ≤2%, the porosity is ≤8%, the volume density is ≥3.72g / cm³, and the surface roughness of the corundum ceramic roller is Rz=92.
[0048] The raw materials in the base material and the surface material are mixed evenly according to the above proportions, and the slurry concentrations of the base material and the surface material are adjusted with deionized water. The slurry viscosity is adjusted to 4-5Pa.s. The base material is first evenly coated on the surface of the prepared corundum ceramic roller by brushing. The base material coating thickness is 0.2μm. It is dried for about 30 minutes under natural conditions. After the base material is half dry, the surface material layer is brushed on the surface of the base material coating. The surface material coating thickness is 0.4μm. It is dried for 24 hours under natural conditions. The surface roughness of the corundum ceramic roller is detected by a roughness meter with an accuracy of 0.01, and Rz=3.8. The service life of the ceramic roller coated with the above anti-corrosion and anti-sticking coating is 150-155 days.
[0049] Example 2
[0050] According to Example 1, the base material formula ratio remains unchanged, the ratio of each raw material of the surface remains unchanged, except that the ratio of HC type and HS in hexagonal boron nitride is adjusted to 1:2, and the coating process is the same as Example 1. Finally, the surface roughness of the corundum ceramic roller is detected to be Rz=4.1. The ceramic roller coated with the above anti-corrosion and anti-sticking coating has a service life of 165-173 days in a roller furnace.
[0051] Example 3
[0052] The ratio of HC type and HS in hexagonal boron nitride was adjusted to 1:3, and the rest was the same as in Example 1. The surface roughness of the corundum ceramic roller was finally detected to be Rz=4.5. The ceramic roller coated with the anti-corrosion and anti-sticking coating had a service life of 153-158 days in a roller furnace.
[0053] Example 4
[0054] A corrosion-resistant and anti-stick ceramic roller coating, wherein the base material comprises 40 kg of silica sol, 30 kg of alumina powder, 25 kg of titanium dioxide, 2 kg of porcelain clay, 0.4 kg of sodium carboxymethyl cellulose, and 2 kg of polyethylene glycol; the outer material comprises 62 kg of silica sol, 8 kg of alumina powder, 10 kg of hexagonal boron nitride, wherein the ratio of HC type to HS type is 1:1, 14 kg of titanium dioxide, 0.8 kg of sodium carboxymethyl cellulose, and 2.8 kg of polyethylene glycol.
[0055] According to the above proportions, the raw materials in the base material and the surface material are mixed evenly, and the slurry concentrations of the base material and the surface material are adjusted with deionized water, and the slurry viscosity is adjusted to 3-4Pa.s. The base material is evenly coated on the surface of the corundum ceramic roller in Example 1 by brushing. The base material coating thickness is 0.1μm. It is dried for about 25 minutes under natural conditions (no wind, heating and exposure). After the base material is half dry, the surface material layer is brushed on the surface of the base material coating. The surface material coating thickness is 0.45μm. It is dried for 24 hours under natural conditions. The surface roughness of the corundum ceramic roller is detected by a roughness meter with an accuracy of 0.01, and Rz=5.7. The ceramic roller coated with the above anti-corrosion and anti-sticking coating has a service life of 140-150 days in a roller furnace.
[0056] Example 5
[0057] A corrosion-resistant and anti-stick ceramic roller coating, wherein the base material comprises 48 kg of silica sol, 33 kg of alumina powder, 18 kg of titanium dioxide, 1 kg of porcelain clay, 0.3 kg of sodium carboxymethyl cellulose, and 1.5 kg of polyethylene glycol; the outer material comprises 65 kg of silica sol, 14 kg of alumina powder, and 12 kg of hexagonal boron nitride, wherein the ratio of HC type to HS type is 1:2, 6 kg of titanium dioxide, 0.8 kg of sodium carboxymethyl cellulose, and 2.5 kg of polyethylene glycol.
[0058] According to the above proportions, the raw materials in the base material and the surface material are mixed evenly, and the slurry concentrations of the base material and the surface material are adjusted with deionized water, and the slurry viscosity is adjusted to 5-6Pa.s. The base material is evenly coated on the surface of the corundum ceramic roller in Example 1 by brushing. The base material coating thickness is 0.25μm. It is dried for about 35 minutes under natural conditions (no wind, heating and exposure to the sun). After the base material is half dry, the surface material layer is brushed on the surface of the base material coating. The surface material coating thickness is 0.3μm. It is dried for 24 hours under natural conditions. The roughness of the corundum ceramic roller coating is detected by a roughness meter with an accuracy of 0.01, and the roughness Rz=4.3. The ceramic roller coated with the above anti-corrosion and anti-sticking coating has a service life of 145-150 days in a roller furnace.
[0059] Example 6
[0060] A corrosion-resistant and anti-stick ceramic roller coating, wherein the base material comprises 46 kg of silica sol, 32 kg of alumina powder, 16 kg of titanium dioxide, 3 kg of porcelain clay, 0.5 kg of sodium carboxymethyl cellulose, and 2.5 kg of polyethylene glycol; the outer material comprises 70 kg of silica sol, 6 kg of alumina powder, and 20 kg of hexagonal boron nitride, wherein the ratio of HC type to HS type is 1:2, 6 kg of titanium dioxide, 0.6 kg of sodium carboxymethyl cellulose, and 1 kg of polyethylene glycol.
[0061] Mix the raw materials in the base material and the surface material evenly according to the above proportions, adjust the slurry concentration of the base material and the surface material with deionized water, adjust the slurry viscosity to 2-3Pa.s, and evenly apply the base material on the surface of the corundum ceramic roller in Example 1 by brushing. The base material coating thickness is 0.2μm. Dry for about 35 minutes under natural conditions (no wind, heating or exposure). After the base material is half dry, brush the surface material layer on the surface of the base material coating. The surface material coating thickness is 0.3μm. Dry for 24 hours under natural conditions. The surface roughness of the corundum ceramic roller is detected to be Rz=3.7. The ceramic roller coated with the above anti-corrosion and anti-sticking coating has a service life of 156-165 days in a roller furnace.
[0062] Example 7
[0063] A corrosion-resistant and anti-stick ceramic roller coating, the base material includes 50 kg of silica sol, 28 kg of aluminum oxide powder, 20 kg of titanium dioxide, 1.5 kg of porcelain clay, 0.3 kg of sodium carboxymethyl cellulose, and 1 kg of polyethylene glycol; the surface material includes 50 kg of silica sol, 15 kg of aluminum oxide powder, 15 kg of hexagonal boron nitride, wherein the ratio of HC type and HS type is 1:2, 15 kg of titanium dioxide, 0.8 kg of sodium carboxymethyl cellulose, and 3 kg of polyethylene glycol. The coating method of the corrosion-resistant and anti-stick ceramic roller coating is the same as that of Example 1, and the surface roughness Rz=6.2 of the corundum ceramic roller is detected by a roughness meter with an accuracy of 0.01. The ceramic roller coated with the corrosion-resistant and anti-stick coating has a service life of 148-158 days in a roller furnace.
[0064] Example 8
[0065] A corrosion-resistant and anti-stick ceramic roller coating, the base material includes 42 kg of silica sol, 31 kg of alumina powder, 22 kg of titanium dioxide, 3 kg of porcelain clay, 0.5 kg of sodium carboxymethyl cellulose, and 2 kg of polyethylene glycol; the surface material includes 70 kg of silica sol, 6 kg of alumina powder, 11 kg of hexagonal boron nitride, wherein the ratio of HC type and HS type is 1:2, 12 kg of titanium dioxide, 0.6 kg of sodium carboxymethyl cellulose, and 1.5 kg of polyethylene glycol. The coating method of the corrosion-resistant and anti-stick ceramic roller coating is the same as that of Example 1, and the surface roughness Rz of the corundum ceramic roller is finally detected to be 5.8. The ceramic roller coated with the corrosion-resistant and anti-stick coating has a service life of 140-146 days in a roller furnace.
[0066] Example 9
[0067] Preparation of corundum ceramic roller: 70 kg of α-alumina powder, 30 kg of plate-shaped corundum, 1.5 kg of activated alumina, 1.5 kg of yttrium oxide kg ratio of the main ingredients, put into the mixer to mix evenly; during the mixing process, use 12kg water to dissolve 0.2kg hydroxypropyl methylcellulose and 2.5kg sodium carboxymethyl cellulose, and spray the solution evenly into the mixer 6 times; the mixed raw materials are put into the vacuum mud kneading machine for vacuum exhaust and mixing evenly, and 3kg of extrusion lubricant edible oil is evenly added in this process, and then extruded into shape in the vacuum extruder with an extrusion pressure of 20bar; dry naturally for 3 days at room temperature, and then slowly increase the temperature of the drying room to 48℃, dry for 2 days, and after drying, sit on the bottom of the kiln furnace and burn upright, lay 2-3 cm thick fused corundum sand on the bottom of the kiln car table, the blank sits on the corundum sand for easy leveling and vertical kiln car table, and in the length direction of the product, use recrystallized silicon carbide brackets every 60 cm to fix the product from multiple points on the side of the product so that it does not move and does not deviate from the position vertical to the kiln car table, and the firing temperature is 1650±5℃.
[0068] The obtained corundum ceramic roller was tested on a universal testing machine, and the flexural strength reached ≥200MPa, the tensile strength ≥280MPa; the water absorption rate ≤3%, the porosity ≤10%, the volume density ≥3.68g / cm³, and the surface roughness of the corundum ceramic roller was Rz=98.
[0069] Example 10
[0070] Preparation of corundum ceramic roller: prepare the main ingredients according to the ratio of 90 kg of α-alumina micropowder, 10 kg of plate-shaped corundum, 3 kg of activated alumina, and 0.5 kg of yttrium oxide, and put them into a mixer to mix evenly; during the mixing process, use 12.5 kg of water to dissolve 1 kg of hydroxypropyl methylcellulose and 0.5 kg of sodium carboxymethyl cellulose, and spray the solution evenly into the mixer in 6 times; put the mixed raw materials into a vacuum mud kneading machine for vacuum exhaust and mixing evenly, and evenly add 5 kg of extrusion lubricant edible oil in this process kg, and then extruded into shape in a vacuum extruder with an extrusion pressure of 25 bar; dried naturally at room temperature for 3 days, and then slowly raised the temperature in the drying room to 45°C and dried for 2 days. After drying, the blank was fired upright in the kiln, and 2-3 cm thick fused corundum sand was laid on the bottom of the kiln car table. The blank was stood on the corundum sand for easy leveling and vertical kiln car table. In the length direction of the product, recrystallized silicon carbide brackets were used every 50 cm to fix the product from multiple points on the side of the product so that it would not move and deviate from the position vertical to the kiln car table. The firing temperature was 1700±5°C.
[0071] After testing, the flexural strength of the corundum ceramic roller produced by the above process reaches ≥250MPa, and the tensile strength reaches ≥340MPa; the water absorption rate is ≤1.5%, the porosity is ≤6%, the volume density is ≥3.8g / cm³, and the surface roughness of the corundum ceramic roller is Rz=80.
[0072] Embodiment 11
[0073] The invention discloses an anti-corrosion and anti-stick ceramic roller for a metal heat treatment furnace. The roller comprises 85 parts of alpha alumina micropowder, 15 parts of plate-shaped corundum, 1 kg of activated alumina and 1.2 kg of yttrium oxide, and the rollers are put into a mixer and mixed evenly. During the mixing process, 0.8 kg of hydroxypropyl methylcellulose and 1.5 kg of sodium carboxymethyl cellulose dissolved in water are sprayed evenly into the mixer in 6 times. The mixed raw materials are put into a vacuum clay kneading machine for vacuum exhaust and mixing evenly. During this process, 4 parts of edible oil as an extrusion lubricant are evenly added, and then the rollers are put into a vacuum kneading machine for vacuum exhaust and mixing evenly. Extrusion molding at the machine, the extrusion pressure is 23bar; natural drying at room temperature for 3 days, then slowly increase the temperature of the drying room to 47℃, dry for 2 days, after drying, sit on the bottom of the kiln and burn upright, lay 2-3 cm thick fused corundum sand on the bottom of the kiln car table, the blank sits on the corundum sand for easy leveling and vertical kiln car table, in the length direction of the product, use recrystallized silicon carbide brackets every 100 cm to fix the product from multiple points on the side of the product so that it does not move and does not deviate from the position vertical to the kiln car table, the firing temperature is 1675±5℃.
[0074] After testing, the flexural strength of the corundum ceramic roller produced by the above process reaches ≥234MPa, and the tensile strength reaches ≥315MPa; the water absorption rate is ≤2%, the porosity is ≤7%, the volume density is ≥3.70g / cm³, and the surface roughness of the corundum ceramic roller is Rz=85.
[0075] Comparative Example 1
[0076] The anti-corrosion and anti-stick coating described in Example 1 is coated on a conventional ceramic roller. Here, the conventional ceramic roller is an ultra-high temperature ceramic roller for a roller kiln disclosed in Chinese Patent Application No. 202110879468.2. The conventional ceramic roller coated with the coating has a service life of 3.5-4 months in a roller furnace, and the corundum roller coated with the coating has a service life of about 5 months in a roller furnace.
[0077] The corundum ceramic roller disclosed in the present invention is composed of pure corundum mineral. According to the result of diffractometer analysis, the corundum content is ≥98%, and the rest is trace impurities. The acid and alkali corrosion resistance and chemical inertness of corundum itself are better than those of mullite. Therefore, even without coating protection, the corundum roller can be used for 20-25 days in a roller furnace, which is longer than the 10-day life of a conventional ceramic roller.
[0078] The anti-corrosion and anti-stick coating disclosed in the present invention includes two layers, a base material layer and a surface layer. The two layers of coating cooperate to extend the service life of the ceramic roller to about 5 months. The base material layer is directly sprayed or brushed on the surface of the ceramic roller, and has strong adhesion and is tightly attached to the ceramic roller. If the surface layer is directly coated on the ceramic roller, it is not tightly attached to the ceramic roller. Even if it is barely attached to the surface of the ceramic roller, it is easy to crack and fall off in flakes after drying or during use. The surface layer and the base material layer coating have strong adhesion, so the base material layer coating needs to be used as an attachment carrier. After the surface layer is worn out after long-term use, the base material layer can also play a certain anti-corrosion role and protect the ceramic roller.
[0079] The surface layer is directly sprayed or brushed on the surface of the base layer, which is neutral or weakly alkaline, and is not easy to react with the liquid FeAlSi ternary alloy phase, so that the coating and the alloy phase will not be chemically reacted and adhered together, so that the running plane of the ceramic roller is smooth, the metal component is less bumpy, and the surface of the metal component will not be scratched. The surface roughness of the anti-corrosion and anti-stick coating is Rz≤6.3, which is nearly 10 times different from the surface roughness of the conventional coating Rz=50. The surface of the anti-corrosion and anti-stick coating is smooth. Therefore, the liquefied ternary alloy phase will slide directly after dripping on the coating, and will not stay on the coating surface, or the stay time is very short. Since the contact time between the liquefied ternary alloy phase and the coating is very short, it is not easy to react with the coating, and it is not easy to corrode the coating, thereby extending the service life of the ceramic roller in the roller furnace. The anti-corrosion and anti-stick coating disclosed by the present invention is a water-based coating, which is non-toxic and easy to clean; it has high temperature resistance, maintains good lubricity and inertness at high temperatures, and has a maximum use temperature of 1000°C in an oxidizing atmosphere and a maximum use temperature of 2200°C in an inert or reducing atmosphere.
[0080] The above is only a preferred embodiment of the present invention. It should be pointed out that for those skilled in the art, several changes and improvements can be made without departing from the overall concept of the present invention, which should also be regarded as the scope of protection of the present invention.
Claims
1. An anti-corrosion and anti-stick coating, characterized in that: It includes base material and fabric. The base material includes 40-50 parts of alkaline silica sol, 28-35 parts of neutral or alkaline α-alumina powder, 15-25 parts of titanium dioxide, 1-3 parts of china clay, 0.3-0.5 parts of sodium carboxymethyl cellulose, and 1-3 parts of polyethylene glycol. The fabric includes 50-70 parts of alkaline silica sol, 6-15 parts of neutral or alkaline α-alumina powder, 10-20 parts of hexagonal boron nitride, 6-15 parts of titanium dioxide, 0.6-0.8 parts of sodium carboxymethyl cellulose, and 1-3 parts of polyethylene glycol. The alkaline silica sol has a pH value of 8-10, an average particle size of 10-20 nm, and a SiO2 content of 25-40%; The neutral or alkaline α-alumina powder has a pH value of ≥7.5, an Al2O3 content of ≥99.5%, an average particle size of ≤2.5 μm, and a conversion rate of ≥95%; The titanium dioxide has a TiO2 content of ≥98%, a pH value of ≥7, and an overall fineness of ≤45 μm; The purity of the hexagonal boron nitride is ≥99.4%. The hexagonal boron nitride is composed of two types: HC type with an average particle size of 9 μm and HS type with an average particle size of 35 μm. The two types of hexagonal boron nitride are mixed in a ratio of 1:1, 1:2, and 1:
3.
2. The use of the anti-corrosion and anti-stick coating according to claim 1, characterized in that: The anti-corrosion and anti-stick coating is coated on the surface of a ceramic or metal substrate, the ceramic is corundum ceramic or AlSi ceramic, and the metal is aluminum, aluminum alloy, stainless steel, or heat-resistant steel.
3. The use of the anti-corrosion and anti-sticking coating according to claim 2, characterized in that: The substrate is in the shape of a tube, a rod or a plate.
4. A corundum ceramic roller, characterized in that: The surface of the ceramic roller is coated with the anti-corrosion and anti-stick coating according to claim 1.
5. The corundum ceramic roller according to claim 4, characterized in that: The raw materials in the base material and the surface of the anti-corrosion and anti-stick coating are mixed evenly according to the proportion, and the slurry concentration of the base material and the surface is adjusted with an appropriate amount of deionized water. The slurry pH value of the base material and the surface is ≥7.
5. The base material and the surface are coated on the surface of the ceramic roller by spraying, brushing or pouring. The base material is coated first, and the surface is coated after the base material is half dry. The base material and the surface are naturally dried after coating.
6. The corundum ceramic roller according to claim 5, characterized in that: The viscosity of the base material and the surface material slurry is adjusted to 2-7Pa.s.
7. The corundum ceramic roller according to claim 5, characterized in that: The thickness of the base coating is 0.1-0.25μm, and the thickness of the surface coating is 0.3-0.45μm.
8. The corundum ceramic roller according to claim 4, characterized in that: The ceramic roller body contains the following main raw materials by weight: 70-90 parts of alpha alumina powder, 1-3 parts of activated alumina powder, 10-30 parts of plate-like corundum, 0.5-1.5 parts of stabilized yttrium oxide; auxiliary materials: 0.2-1 parts of hydroxypropyl methylcellulose, 0.5-2.5 parts of sodium carboxymethyl cellulose, 3-5 parts of edible oil, and 12-13 parts of water.
9. The method for preparing the corundum ceramic roller according to claim 8, characterized in that: The following steps are included: (1) Mix α-alumina powder, activated alumina powder, plate-shaped corundum and stabilized yttrium oxide in proportion and put them into a mixer to mix evenly; (2) During the mixing process, hydroxypropyl methylcellulose and sodium carboxymethyl cellulose dissolved in water are evenly sprayed into the mixer several times; (3) The mixed raw materials are put into the vacuum clay machine for vacuum exhaust and uniform mixing. During this process, edible oil as extrusion lubricant is evenly added, and then extruded into shape in the vacuum extruder with an extrusion pressure of 20-25 bar; (4) After drying, it is fired upright in a kiln at a temperature of 1650-1700℃.
10. The method for preparing the corundum ceramic roller according to claim 9, characterized in that: Step (4) drying refers to natural drying at room temperature for 3 days, then slowly raising the drying room temperature to 45-50°C and drying for 2 days.
11. The method for preparing the corundum ceramic roller according to claim 9, characterized in that: Step (4) bottom-standing firing means laying 2-3 cm thick fused corundum sand on the bottom of the kiln car table. The blank is placed on the corundum sand for easy leveling and vertical to the kiln car table. Recrystallized silicon carbide brackets are used every 50-100 cm along the length of the blank to fix the blank at multiple points on the side of the blank so that it does not move and does not deviate from the position vertical to the kiln car table.
Citation Information
Patent Citations
Ultrahigh-temperature ceramic roller bar for roller kiln and preparation method thereof
CN113416084A
Coating composition for metal substrates
AU2002331144B2
Ultrahigh-temperature high-strength ceramic roller and preparation method thereof
CN110894162A